Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Chen, Y; Ran, Z; Wang, Y-N; Liu, X; Yang, P; Han, K; Yin, X; Zou, C; Wu, R; Mao, H; Jin, T (Springer Nature, 2023)
Traffic emissions are a major source of ambient air pollution, and exposure to these emissions has been linked to numerous adverse health effects. Our study investigated the reduction of traffic emissions in downtown Tianjin, China, and assessed its health benefits. Based on the vehicle emission inventory, The Atmospheric Dispersion Modelling System (ADMS) was adopted for simulating the dispersion of traffic-related air pollutants including primary fine particulate matter (PM2.5), and carbon monoxide (CO). The Benefits Mapping and Analysis Program (BenMAP) was then used to quantify the benefits of emission reductions with respect to cardiovascular disease and respiratory disease. We found a downward trend in PM2.5 and CO concentrations from 2015 to 2019 (PM2.5: 17.8 to 10.5μg/m3, CO: 2.3 to 1.3mg/m3). Furthermore, in line with the reduction of average annual PM2.5 and CO attributable to traffic emissions during 2016–2019 compared with 2015, the accumulative deaths from the two diseases mentioned above in these years decreased by 156 and 961 respectively. Our study constructs an integrated framework combining emission inventories, air quality modeling, and population health benefits, which can be used for further health effects of related air quality improvement.